Combination of circulating CXCR4 and Bmi-1 mRNA in plasma: A potential novel tumor marker for gastric cancer - Xu, Wenrong; Zhou, Hongxing; Qian, Hui; Bu, Xuefeng; Chen, Deyu; Gu, Hongbing; Zhu, Wei; Yan, Yongmin; Mao, Fei (Molecular medicine reports, 2009)
Cell-free nucleic acids in plasma have been reported to be a novel tumor marker. However, their exact significance in gastric cancer is unclear. In the present study, we focused on circulating CXCR4 and Bmi-1 mRNA in plasma and evaluated their diagnostic values for patients with gastric cancer. CXCR4 and Bmi-1 mRNA levels, as well as levels of CEA and CA19-9 proteins, were determined in the plasma of 89 gastric cancer patients. The levels of these markers were significantly higher in cancer patients than in healthy subjects; however, there was a decrease in their expression after surgery. The sensitivity of detection for the combination of circulating CXCR4 and Bmi-1 mRNA was higher than the sensitivities of detection for CEA and CA19-9. In patients expressing both genes, CXCR4 and Bmi-1 mRNA levels were strongly correlated. Expression of the two circulating genes was also strongly correlated with the CEA level, and was significantly associated with the age of the patient, histological type, clinical stage, extent of cell differentiation and gastric cancer metastasis. Our results indicate that the combined expression of circulating CXCR4 and Bmi-1 mRNA represents a novel tumor marker, superior to traditional markers such as CEA and CA19-9, for the diagnosis and monitoring of gastric cancer.